Laws of Gravitation and Motion in the Ancient Indian Texts - Sarmah Pathak, Jumisree (International Journal of Applied Sciences and Smart Technologies, 2024)
In this study, various verses from the Vedic Texts, which directly explains the fundamental laws of Gravitation and Motion in physical science are summarized. The correlation of each verse (mantra/ shloka) to the existing fundamental theory of Physical science shows the compatibility of Physical science with the Vedic Texts and we hope that the thorough analysis of all these ancient texts may open door to many probable insights to the undiscovered fundamental laws of basic science and its applications. Keywords: Gravitation, Laws of Motion, Physical Science, Vaisheshika Sutra, Veda